Impact of Cesarean Section Number on Maternal and Obstetric Outcome - Deniz Arıkan; Ayhan Coşkun; Ali Özer; Hakan Kıran; Abdullah Tok; Ender Zencir (Medical Network, 2009)
OBJECTIVE: We aimed to evaluate the maternal and obstetric outcomes associated with increasing number of cesarean sections (C/Ss). STUDY DESIGN: The clinical records of 408 women who were delivered by C/S at our clinic were examined for some maternal and neonatal outcomes, retrospectively. The pregnant women were assigned to groups based on previous number of C/S; group 1 was consisted of the cases that had no C/S, group 2 one C/S, group 3 two C/Ss and group 4 three and more C/Ss. RESULTS: The most common indication for first C/S was fetal distress with 60 ( 30.3% ) of 198 cases. Mean maternal age, gestational age, birth weight, 1 and 5 minute Apgar scores, operating time, difference of post-op and pre-op hemoglobin level, and length of postoperative hospitalization were similar among groups (p>0.05). The ratio of placenta previa, and blood transfusion were significantly high in group 4 compared to group 1, 2, and 3 (p<0.05). Hysterectomy was performed in 5 (1.5%) cases and maternal mortality occured in 2 (0.6%) cases. CONCLUSION: Among the causes of morbidity clinically most important was the triad of placenta previa, placenta accreta and hysterectomy, was also responsible for the most serious risk to the mother with increasing number of C/S.